2021
DOI: 10.1016/j.cegh.2021.100785
|View full text |Cite
|
Sign up to set email alerts
|

Multivariate approach in analyzing medical data with correlated multiple outcomes: An exploration using ACCORD trial data

Abstract: Background: In clinical setting, to answer a research question, very often more than one outcome variables are used which are statistically correlated. Univariate analysis approach, which is commonly used in such context, violates the assumption of independence for correlated variables, while multivariate approach could give more robust and precise clinical decision by accounting this correlation. This paper is a demonstration of the change in statistical decision in multivariate approach compared to univariat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 22 publications
(34 reference statements)
0
2
0
Order By: Relevance
“…In these models, all hippocampal subfields are entered as one outcome, resulting in a single model per each psychosocial factor (see Code S1 ). Previous literature has shown that multivariate approaches increase the power of the model as well as reduce type I error compared with univariate approaches that ignore the correlation between outcomes (Mishra et al, 2021 ). While in univariate analyses, one can adjust the p value, the assumption of independence between outcomes is violated when they are correlated.…”
Section: Methodsmentioning
confidence: 99%
“…In these models, all hippocampal subfields are entered as one outcome, resulting in a single model per each psychosocial factor (see Code S1 ). Previous literature has shown that multivariate approaches increase the power of the model as well as reduce type I error compared with univariate approaches that ignore the correlation between outcomes (Mishra et al, 2021 ). While in univariate analyses, one can adjust the p value, the assumption of independence between outcomes is violated when they are correlated.…”
Section: Methodsmentioning
confidence: 99%
“…9 Multivariate analysis which accounts for these correlations in making inferences is the correct method for analysing such data and various authors have attempted this in medical data analysis. 10,11 Further, the above mentioned correlation of the primary outcome variables is likely to exist while pooling such effect measures in metaanalysis. Hence, not adjusting for this correlation in the meta-analysis might produce effect measures with compromised precision.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, multivariate analyses are a preferable approach when analysing complex datasets, providing a more realistic basis for robust and accurate clinical decisions [6]. Moreover, multivariate analysis enables the assessment of the contribution of multiple factors concerning one or more clinical factors to reflect reality, reveal relationships between the factors analysed, and reduce the bias of univariate patient characteristics across studies [6][7][8][9]. Nowadays, several multivariate approaches are available that consider complex, multidimensional relationships between factors.…”
Section: Introductionmentioning
confidence: 99%